Morinda officinalis oligosaccharides ameliorate depressive‐like behaviors in poststroke rats through upregulating GLUT3 to improve synaptic activity. Issue 10 (19th August 2020) - Zhu, Jiayi; Peng, Qiwei; Xu, Yi; Xu, Hexiang; Wan, Yan; Li, Zhifang; Qiu, Yanmei; Xia, Wenguang; Guo, Zhenli; Li, Hongkai; Jin, Huijuan; Hu, Bo
Abstract: Poststroke depression (PSD) is one of the most common psychiatric diseases afflicting stroke survivors, yet the underlying mechanism is poorly understood. The pathophysiology of PSD is presumably multifactorial, involving ischemia‐induced disturbance in the context of psychosocial distress. The homeostasis of glucose metabolism is crucial to neural activity. In this study, we showed that glucose consumption was decreased in the medial prefrontal cortex (mPFC) of PSD rats. The suppressed glucose metabolism was due to decreased glucose transporter‐3 (GLUT3) expression, the most abundant and specific glucose transporter of neurons. We also found Morinda officinalis oligosaccharides (MOOs), approved as an antidepressive Chinese medicine, through upregulating GLUT3 expression in the mPFC, improved glucose metabolism, and enhanced synaptic activity, which ultimately ameliorated depressive‐like behavior in PSD rats. We further confirmed the mechanism that MOOs induce GLUT3 expression via the PKA/pCREB pathway in PSD rats. Our work showed that MOOs treatment is capable of restoring GLUT3 level to improve depressive‐like behaviors in PSD rats. We also propose GLUT3 as a potential therapeutic target for PSD and emphasize the importance of metabolism disturbance in PSD pathology.